Seed germination requirements of four species co-occurring in a Wisconsin sedge meadow - (:unkn) unknown (My University, 1992)
Seeds of four colonizing species which occur together in a recently revegetated sedge meadow were tested for germination after storage under three different conditions. Seeds were tested at an alternating temperature regime of 21° C dark, and 32° C light. Three species, Bidens frondosa, B. coronata, and Scirpus cyperinus germinated most successfully when stored under moist-cool conditions. Germination of Carex scoparia was consistently high and was not affected by storage condition. Differences in seed germination among the four species may contribute to their coexistence in highly disturbed environments such as newly revegetated sedge meadows.
Keywords: seed germination; sedge meadow; Bidens frondosa; Bidens coronata; Scirpus cyperinus; Carex scoparia